On Hardy-Pachpatte-Copson's Inequalities - Chang-Jian Zhao; Wing-Sum Cheung (The Scientific World Journal)
We establish new inequalities similar to Hardy-Pachpatte-Copson’s type inequalities. These results in special cases yield some of the recent results.